FORMULATING RESEARCH PROBLEMS AND DEVELOPING HYPOTHESES IN QUANTITATIVE DA'WAH STUDIES: A SYSTEMATIC-CONTEXTUAL INTEGRATION FOR ENHANCED DA'WAH MESSAGE IMPACT - Risqiatul Hasanah; Nuril Huda; Dina Hermina (Indonesian Journal of Islamic Communication, 2025)
This study explores the formulation of problems and the development of hypotheses in quantitative da'wah research through the integration of systematic and contextual approaches. In response to the growing complexity of Islamic communication in contemporary society, this research proposes a hybrid methodology that reinforces the relevance, precision, and impact of da'wah messages. Utilizing a descriptive-analytical method, the study synthesizes data from scholarly articles and empirical evidence to identify key components of problem formulation, including goal identification, condition mapping, and strategic selection, and connects them with culturally responsive hypothesis construction. The findings reveal that systematic approaches ensure methodological coherence and reproducibility, while contextual insights enhance cultural and social resonance. Together, they create a comprehensive framework for developing impactful hypotheses in da'wah research. This integrated strategy not only elevates the quality of Islamic discourse but also strengthens the alignment between da'wah messages and audience needs, ultimately enhancing the effectiveness of religious communication in diverse societal settings.